2023
DOI: 10.1007/s00405-023-07865-6
|View full text |Cite
|
Sign up to set email alerts
|

FraMaDySc: dysphagia screening for patients after surgery for head and neck cancer

Abstract: Purpose Oropharyngeal dysphagia is one of the most common postoperative consequences in head and neck cancer patients. Above all, these patients often suffer from aspiration and limitations of oral intake. However, no reliable dysphagia screening is available for this target group. This study aimed to develop and validate a screening, FraMaDySc, based on a water swallow test (WST) for the identification of postsurgical patients with a risk of aspiration, limitations of oral intake, and, as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…Therefore, we determined their eligibility for inclusion in the study through calculations. Horii et al 19 and Hey et al 10 reported sensitivity, specificity, positive LR, and negative LR, while Patterson et al 13 provided information on sensitivity, specificity, TP, actual positive cases, TN, and actual negative cases. We calculated the values for the 2 × 2 contingency tables using the Revman 5.3 calculator.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we determined their eligibility for inclusion in the study through calculations. Horii et al 19 and Hey et al 10 reported sensitivity, specificity, positive LR, and negative LR, while Patterson et al 13 provided information on sensitivity, specificity, TP, actual positive cases, TN, and actual negative cases. We calculated the values for the 2 × 2 contingency tables using the Revman 5.3 calculator.…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to the standardization of testing performance and failure criteria in the modified WST, thereby minimizing subjectivity. 10 Furthermore, whether it is the incremental WST or the 100 mL WST, increasing water volume can reduce the risk of aspiration, and the use of failure criteria (wet sounds and coughing) can ensure patient safety. 10,12 Hence, future investigations can explore the application of the modified WST in HNC patients with diverse tumor sites and treatment to further assess its reliability in screening.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations